Mike Benoit at a party at Émile Benoit's house for the visiting folklore class - Merrigan, Shirley (1988)
Photo faisant partie d'une série associée à une dissertation trimestrielle d'étudiant(e) en folklore à l'université Memorial: « Folklore Field Trip to Black Duck Brook and Cape St. George March 12-March 16 1988: A Report ». -- Photo is one of a series associated with a Memorial University folklore student term paper: "Folklore Field Trip to Black Duck Brook and Cape St. George March 12-March 16 1988: A Report".